To analyze the information provided, let's start by identifying the parent function and the transformed function.
The vertex of a quadratic function is given in the form:
\[ y = a(x-h)^2 + k \]
where \((h, k)\) is the vertex of the parabola. Here, the vertex is given as \((-2, 0)\), which means \(h = -2\) and \(k = 0\).
The parent function (without any transformations) is:
\[ y = x^2 \]
Now, incorporating the vertex into the vertex form of a quadratic function, we have:
\[ y = a(x - (-2))^2 + 0 \implies y = a(x + 2)^2 \]
Since there is no additional information to indicate a stretching or compressing factor (the value of \(a\) is not specified), we can assume \(a = 1\) for the basic transformation, leading us to:
\[ y = (x + 2)^2 \]
So, the final answers are:
- The parent function is \(y = x^2\).
- The equation of the transformed function is \(y = (x + 2)^2\).
Now let's match this to your options:
The correct response from your options is:
"The parent function is y = x^2. The equation of the transformed function is y = (x + 2)^2."